Hypersensitivity pneumonitis: Main features characterization in a Portuguese cohort - Santos, V (2020)
Hypersensitivity pneumonitis (HP) is an interstitial lung disease (ILD) which varies in prevalence across the world, depending on disease definition, diagnostic methods, exposure type and intensity, geographical environments, agricultural and industrial practices, and host risk factors. This study aimed to deepen knowledge about HP's clinical characteristics, diagnosis and functional and imaging features in a cohort of HP patients from the North of Portugal. To achieve this goal, a retrospective assessment of the clinical and diagnostic data was carried out, and patients were classified and compared according to disease presentation (acute, sub-acute and chronic HP forms). Of the 209 HP patients included (mean age 58.3 ± 16.0 years), 52.6% were female and 73.7% presented a chronic form. Most patients had prior exposure to birds (76.6%). Dyspnoea and cough were the most frequently experienced symptoms, but no statistically significant differences were found between groups (p = 0.089, p = 0.418, respectively). Fever was most common in acute HP form (p < 0.001). The most common patterns found in Chest CT were ground glass (p = 0.002) in acute/subacute presentation, and reticulation (p < 0.001) in chronic form, while mosaic attenuation, although was also frequently observed, no statistically significant differences were found between groups (p = 0.512). The most common functional pattern was restrictive (38% of patients, 73.7% with chronic HP form). Bronchoalveolar lavage lymphocytes were higher in acute and subacute forms although not reaching statistical significance (p = 0.072), with lowest CD4/CD8 ratio (p = 0.001) in acute forms. Thus, given the significant disease heterogeneity, further studies with different populations and ambient exposures are needed to achieve a better stratification of the exposure risk, to provide proper implementation of avoidance methods and a precise diagnostic and therapeutic approach.